Exosomes derived from tumor adjacent fibroblasts efficiently target pancreatic tumors - Saini Setua; Shabia Shabir; Poornima Shaji; Ana Martinez Bulnes; Anupam Dhasmana; Swathi Holla; Nivesh K. Mittal; Nirakar Sahoo; Tripti Saini; Francesco Giorgianni; Mohammad Sikander; Andrew E. Massey; et al. (Elsevier, 2024)
The application of extracellular vesicles, particularly exosomes (EXs), is rapidly expanding in the field of medicine, owing to their remarkable properties as natural carriers of biological cargo. This study investigates utilization of exosomes derived from stromal cells of tumor adjacent normal tissues (NAF-EXs) for personalized medicine, which can be derived at the time of diagnosis by endoscopic ultrasound. Herein, we show that exosomes (EXs) derived from NAFs demonstrate differential bio-physical characteristics, efficient cellular internalization, drug loading efficiency, pancreatic tumor targeting and delivery of payloads. NAF-derived EXs (NAF-EXs) were used for loading ormeloxifene (ORM), a potent anti-cancer and desmoplasia inhibitor as a model drug. We found that ORM maintains normal fibroblast cell phenotype and renders them incompatible to be triggered for a CAF-like phenotype, which may be due to regulation of Ca2+ influx in fibroblast cells. NAF-EXs-ORM effectively blocked oncogenic signaling pathways involved in desmoplasia and epithelial mesenchymal transition (EMT) and repressed tumor growth in xenograft mouse model. In conclusion, our data suggests preferential tropism of NAF-EXs for PDAC tumors, thus imply feasibility of developing a novel personalized medicine for PDAC patients using autologous NAF-EXs for improved therapeutic outcome of anti-cancer drugs. Additionally, it provides the opportunity of utilizing this biological scaffold for effective therapeutics in combination with standard therapeutic regimen.